The effects of early rehabilitation on functional exercise tolerance in decompensated heart failure patients: Results of a multicenter randomized controlled trial (ERIC-HF study) - Delgado, Bruno (2022)
Objective: To analyze (1) the effect of an aerobic training program on functional exercise tolerance in decompensated heart failure (DHF) patients; (2) to assess the effects of an aerobic training program on functional independence; and (3) dyspnea during activities of daily living. Design: A randomized controlled clinical trial with follow-up at discharge. Settings: Eight hospitals. Recruitment took place between 9/ 2017 and 3/2019. Group Assignments: Patients with DHF who were admitted to the hospital, were randomly assigned to usual rehabilitation care guideline recommended (control group) or aerobic training program (exercise group). Main outcome: Functional exercise tolerance was measured with a 6-min walking test at discharge. Results: In total 257 patients with DHF were included, with a mean age of 67±11 years, 84% (n=205) had a reduced ejection fraction and the hospital stay was 16±10 days. At discharge, patients in the intervention group walked further compared to the control group (278±117m vs 219±115m, p < 0.01) and this difference stayed significant after correcting for confounders (p < 0.01). A significant difference was found favoring the exercise group in functional independence (96±7 vs 93±12, p=0.02) and dyspnea associated to ADL (13±5 vs 17±7, p < 0.01) and these differences persisted after correcting for baseline values and confounders (functional independence p < 0.01; dyspnea associated with ADL p=0.02). Conclusion: The ERIC-HF program is safe, feasible, and effective in increasing functional exercise tolerance and functional independence in hospitalized patients admitted due to DHF.